PROGRAM SAMTAMA (SAMPAH TANGGUNG JAWAB BERSAMA) DI BANJARMLATI KOTA KEDIRI - Reny Nugraheni; Ekawati Wasis Wijayati, Krisnita Dwi Jayanti, Marianingsih (JOURNAL OF COMMUNITY DEDICATION, 2022)
The rapid development and growth of population every year in urban areas has resulted in increasingly large and denser residential areas. The increase in human activity every year is increasing as well as the increase in waste in the area. Basically, waste can be divided into two types, namely organic waste and inorganic waste. Organic waste is waste that decomposes easily and can be processed directly into compost. The importance of providing education to the public in waste sorting. This community service is carried out by counseling and demonstration methods to the community in Banjarmlati. With a total of 48 respondents. The results of the counseling and demonstration of organic waste management with the Takakura method and adorganic waste management, namely an increase in public knowledge about waste management in Banjarmlati.